Chromosome-Level Genome Assembly and Annotation of the Highly Heterozygous Phallus echinovolvatus Provide New Insights into Its Genetics - Mengya An; Ruoxi Liang; Yanliu Chen; Jinhua Zhang; Xiuqing Wang; Xing Li; Guohua Qu; Junfeng Liang (Journal of Fungi)
Phallus echinovolvatus is a well-known edible and medicinal fungus with significant economic value. However, the available whole-genome information is lacking for this species. The chromosome-scale reference genome (Monop) and two haploid genomes (Hap1 and Hap2) of P. echinovolvatus, each assembled into 11 pseudochromosomes, were constructed using Illumina, PacBio-HiFi long-read sequencing, and Hi-C technology. The Monop had a size of 36.54 Mb, with 10,251 predicted protein-coding genes and including 433 carbohydrate-active enzyme genes, 385 cytochrome P450 enzyme genes, and 42 gene clusters related to secondary metabolite synthesis. Phylogenetic and collinearity analysis revealed a close evolutionary relationship between P. echinovolvatus and Clathrus columnatus in the core Phallales clade. Hap1 and Hap2 had sizes of 35.46 Mb and 36.11 Mb, respectively. Collinear relationships were not observed for 15.38% of the genes in the two haplotypes. Hap1 had 256 unique genes, and Hap2 had 370 unique genes. Our analysis of the P. echinovolvatus genome provides insights into the genetic basis of the mechanisms underlying the metabolic effects of bioactive substances and will aid ongoing breeding efforts and studies of genetic mechanisms.